2017
DOI: 10.4236/msce.2017.52006
|View full text |Cite
|
Sign up to set email alerts
|

Forced Electrocodeposition of Silica Particles into Nickel Matrix by Horizontal Impinging Jet Cell

Abstract: The improvement of silica particle codeposition into a nickel electrodeposited composite coating (ECC) by a double face horizontal impinging jet cell (IJC) has been studied. The microstructure of coatings was examined by means of scanning electron microscopy performed in backscattered electron mode. The embedded particles distribution was shown to be the densest and the most uniform in laminar low flow mode and when the nozzle is at a distance of 5 mm close from the cathode. Excrescences observed on the compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Nickel Ni, nickel-silicon Ni-Si, and Ni-Silicon carbide Ni-SiC coatings have been prior electrodeposited onto the substrate XC100 through a Watts-type bath. 30,31 1 wt% of silicon (Alfa Aesar; 1 -5 µm) and silicon carbide (Goodfellow; 0.1 -1 µm) were embedded respectively into Ni-Si and Ni-SiC Composite coatings.…”
Section: Experimental Materials and Thermal Treatmentmentioning
confidence: 99%
“…Nickel Ni, nickel-silicon Ni-Si, and Ni-Silicon carbide Ni-SiC coatings have been prior electrodeposited onto the substrate XC100 through a Watts-type bath. 30,31 1 wt% of silicon (Alfa Aesar; 1 -5 µm) and silicon carbide (Goodfellow; 0.1 -1 µm) were embedded respectively into Ni-Si and Ni-SiC Composite coatings.…”
Section: Experimental Materials and Thermal Treatmentmentioning
confidence: 99%
“…The effects of different nanofillers on mechanical properties, wear resistance, and corrosion resistance of the coatings were investigated. It was found that the properties of the coatings can be significantly improved by adding nanofillers such as silicon carbide (SiC) [28,29], silicon dioxide (SiO2) [30], aluminum oxide (Al2O3) [31][32], titanium nitrate (TiN) [33], carbon nanotubes (CNTs) [34] to the matrix.…”
Section: Introductionmentioning
confidence: 99%